KAJIAN LITERATUR SISTEM INFORMASI MANAJEMEN STOK - Putra, Guntur Maulana; Nurul Huda, Sheila (STKIP PGRI Situbondo, 2025)
Information systems have a big role in the needs of a company, information systems optimize the business world, especially now with the increasingly advanced development of science and technology, the role of information systems has a big influence on the progress of a company or business. The research entitled